Active temporal multiplexing of indistinguishable heralded single photons - C. Xiong (Nature Portfolio, 2016)
Deterministically generated single photons are useful for quantum communications, but the processes that create such light are often non-deterministic. Here, the authors enhance the single-photon output probability by multiplexing photons from four temporal modes using fibre-integrated optics.